The Influence of Qawāid Mastery on Mahāratul Kitābah Class XI MAN 1 Students in Gorontalo City - Djalil, Rasmi; Hairuddin, Hairuddin; I. Miolo, Mukhtar (Al-Kalim : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
This study aims to determine the effect of mastery of qawa>id on maha>ratul kita>bah of class XI students at MAN 1 Gorontalo City. The research method used is a research method with an experimental quantitative approach, which seeks the influence of the independent variable on the dependent variable. The population taken in this study was all class XI at MAN 1 Gorontalo City with a sample of 55 students. The data collection techniques in this study were observation, interview and documentation. The data collection model uses tests. The data were analyzed using simple correlation test with the help of spss 25 for windows application. The results of this study indicate that the result of the simple regression equation of mastery of qawa'id on the ability to write Arabic text is 0.000% with a very high significant level. So, there is a relationship or influence between the mastery of qawa'id on the ability to write Arabic text. Based on the probability value of 0.000 <0.05 and in the model summary table by looking at R Square = 0.600 or 60%, it can be interpreted that the variable mastery of qawa'id (X) has an influence on the variable ability of maha>ratul kita>bah of Class XI students at MAN 1 Gorontalo City (Y) by 60%.